Human Capital and Production Structure in the Greek Economy Knowledge, Abilities, Skills - Petrakis, Panagiotis E. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
The role of human capital has diversified considerably in the last 100 years. Today, the prevailing perception seeks a sustainable, integrated development which is based on the triptych of environment, economy, and society. In this mode of development, human capital has a positive effect on the economy, on social cohesion and optimal governance, as well as on the ecological footprint. This book studies the critical role of human capital in the Greek economy and its production structure. In doing so, this book analyzes the Greek labor market, employment, and structural changes, among other facets of this vibrant economy. This is an inspiring book, full of important insights for those of us who want to know about the upgraded role of human capital in a world that seeks sustainable development combining the environment, the economy and society. It is a must-read primer for anyone interested in the positive effects of human on the economy, social cohesion and optimal governance. Evangelia Papapetrou - Professor in the Department of Economics of the National and Kapodistrian University of Athens, Greece. This captivating book is a modern attempt to examine the role of human capital, using knowledge, abilities, skills and working activities as the key drivers to guide an economy to its structural change. Focusing on the Greek case, the authors provide pragmatic insights on the role of human capital on economic structural change, the structural relationships and the need for restructuring and the critical role of life-long learning. Stylianos Kotsios - Professor and Chairman of the Department of Economics of the National and Kapodistrian University of Athens in Greece. .
Part A: Human Capital and Structural Change -- Chapter 1: The Role of Human Capital in Economic Development in the 21st Century -- Chapter 2: Human Capital and Structural Economic Transformation -- Chapter 3: Occupational Characteristics Analysis -- Chapter 4: Productive Structure, Technological Change and Requirements in Human Capital -- Part B: Structural Relations and Structural Changes in the Greek Economy -- Chapter 5: Sectoral Analysis of the Economic Activity of the Greek Economy, Input - Output Analysis -- Chapter 6: Estimation of the Medium-term Demand for Occupations and Specialities in the Greek Economy Using an Input - Output Analysis -- Part C: Analysis of Human Capital Requirements in Greece -- Chapter 7: Restructuring the Greek Labor Market During the Last Two Economic Crises -- Chapter 8: The European Experience in Lifelong Learning and the Restructuring of the Economy -- Chapter 9: Labor Market Analysis Based on the Knowledge, Skills, Abilities and Working Activities of Employees in the Present and Future Production Structure of 2027.
Keywords: Labor economics; Economics; Macroeconomics; Labor Economics; Political Economy and Economic Systems; Macroeconomics and Monetary Economics